Impact of Combined Grazing by Prairie Dogs with Goats or Cattle on Vegetation and Hydrology of a Chihuahuan Desert Grassland - Mellado, M; Olvera, A; Duenez, J; Mellado, J (Annals of Arid Zone, 2016)
Impact of combined grazing by prame dogs with goats or cattle onvegetation and hydrology of a Chihuahuan desert grassland of northern Mexicowas assessed. Twice replicated grazing treatments were: (1) yearlong continuousgoat grazing at a high intensity in a prairie dog colony, and (2) sequential rotation grazingby cattle along with prairie dogs at a moderate intensity. The pasture grazed byprairie dogs with cattle supported fewer plant species (n = 50) than the pasturegrazed by goats with prairie dogs (n = 63). The synergistic grazing by goats andprairie dogs caused a 68% reduction in the aboveground biomass, with a directionalchange favoring herbaceous vegetation at the expense of grasses. The average biomassproduction of forbs increased 65% and the average grass standing crop decreasedby 400% under the combined grazing regime of prairie dogs and goats, in comparisonto the pasture grazed by prairie dogs and cattle. Most forbs with higher contributionto the total standing crop on the site grazed by prairie dogs and goats were non-edible.The standing crop of shrubs was higher (P